2021
DOI: 10.1136/annrheumdis-2021-220408
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccination in rituximab-treated patients: evidence for impaired humoral but inducible cellular immune response

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
127
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(152 citation statements)
references
References 6 publications
14
127
2
9
Order By: Relevance
“…However, it remains unclear whether, or to which extent, repopulation of peripheral B cells is needed for antibody development in RTX-treated patients. 15 To determine if or for how long it might be useful to withhold COVID-19 vaccination in RTX-treated patients, we assessed the cellular and humoral immune response and related it to numbers of peripheral B cells.…”
Section: Miscellaneousmentioning
confidence: 99%
“…However, it remains unclear whether, or to which extent, repopulation of peripheral B cells is needed for antibody development in RTX-treated patients. 15 To determine if or for how long it might be useful to withhold COVID-19 vaccination in RTX-treated patients, we assessed the cellular and humoral immune response and related it to numbers of peripheral B cells.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Indeed, available data are still too limited to suggest treatment discontinuation in order to favor a vaccination response, considering the significant risk of clinical relapse and MRI activity associated to second-line treatment withdrawal (at least in relapsing–remitting MS patients). Furthermore, initial reports relative to other medical conditions causing immunodeficiency suggest the possibility of an efficient cell-mediated immunity after vaccination even in the absence of a detectable humoral response [ 10 ].…”
mentioning
confidence: 99%
“…We read with a great interest the article published by Bonelli et al suggesting an inducible cellular immune response in rituximab (Rtx) treated patients. 1 The CD20-antibody Rtx is one of the most widespread biologicals worldwide with a broad spectrum of oncological and rheumatological indications. Due to its depleting effect on circulating B cells, the generation of antibodies against novel pathogens is impaired in Rtx-treated patients.…”
mentioning
confidence: 99%
“…7 Fortunately, very recent data by Bonelli et al have now suggested that a cellular response is mounted after SARS-CoV-2 vaccination in Rtxtreated patients despite a failed humoral immune response. 1 The authors demonstrated that peripheral blood cells of vaccinated patients do produce Interferon γ (IFNγ) after stimulation with SARS-CoV-2 spike (S) protein-derived overlapping peptides. 1 These results increase the scientific interest into a more detailed characterisation of vaccine-reactive T-cell immunity, which has recently been in the focus of our group as well due to a frequent Rtx application in our settings.…”
mentioning
confidence: 99%